2009
DOI: 10.1007/s10637-009-9308-7
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the time-course of myelosuppression from rats to patients with a semi-physiological model

Abstract: This method for interspecies scaling was successful in predicting the time-course of myelosuppression in patients based on rat data. Predictions improved when species differences in protein binding and CFU-GM assay sensitivity were accounted for. The approach appears promising for predicting myelosuppression in patients early in development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 36 publications
0
60
1
Order By: Relevance
“…frequency of dosing or infusion time) can lead to very distinct neutrophil dynamics and incidence of neutropenia [22], [27], [34], [36], [39][42]. Therefore, we used the Friberg model of neutropenia to study in detail how drug plasma time course correlated with incidence or severity by employing previously published semi-mechanistic population PK-PD models (Figure 1a) built from clinical ANC profiles following treatment with docetaxel [26], [34].…”
Section: Resultsmentioning
confidence: 99%
“…frequency of dosing or infusion time) can lead to very distinct neutrophil dynamics and incidence of neutropenia [22], [27], [34], [36], [39][42]. Therefore, we used the Friberg model of neutropenia to study in detail how drug plasma time course correlated with incidence or severity by employing previously published semi-mechanistic population PK-PD models (Figure 1a) built from clinical ANC profiles following treatment with docetaxel [26], [34].…”
Section: Resultsmentioning
confidence: 99%
“…The most used and accepted model was developed by Friberg et al (2002), hereafter the reference model, which has demonstrated consistency among a wide variety of anticancer agents (Latz et al, 2006;Fetterly et al, 2008;Soto et al, 2010b) and has been used to describe neutropenic effects after drug combinations (Sandstrom et al, 2005;Soto et al, 2010a) and predict human hematologic toxicity from laboratory animal data (Friberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among these approaches, the model developed by Friberg et al [9] has been applied repeatedly to describe the time course of myelosuppression after administration of several cytotoxic anticancer drugs [12][13][14][15][16][17][18][19]. In addition, this model has successfully been applied in the scaling of the time course of myelosuppression from rat data to patients showing its usefulness in the drug development process [20].…”
Section: Introductionmentioning
confidence: 99%